Experimental study of relationships between sizing force and deformation of sintered parts to define process control procedure. (December 2014) - Cristofolini, I.; Fontanari, V.; Belluzzi, D.; Pederzini, G.; Molinari, A.
Abstract : Sizing is studied in this work as a post-sintering operation aimed at improving the dimensional and geometrical precision of sintered parts. The required dimensional and geometrical characteristics are obtained by the plastic deformation due to sizing, which is related to the applied stress. In this work, the relationships between applied force, resulting deformation, attainable geometrical characteristics have been investigated. By means of the data recorded by a hydraulic press, force–displacement curves have been derived. The analysis of these curves allowed identifying the elastic deformation of part and tool, as well as the plastic deformation of the part. The plastic deformation has been correlated to the actual dimensional changes measured on the part, as well as to the change in the required geometrical characteristic (conicity). On the basis of these relationships, a design procedure to optimise the sizing strategy has been proposed.